MICROBIAL COMMUNITIES AND ENZYME KINETICS USED AS INDEX OF RECLAMATION IN A CHRONOSEQUENCE COAL MINE OVERBURDEN SPOIL - JITESH KUMAR MAHARANA; AMIYA KUMAR PATEL (International Journal of Pharma and Bio Sciences, 2013)
Restoration ecology is required to access the role(s) of microorganisms in facilitating mine spoil genesis, activity, biodiversity, ecosystem function, and metabolic response as a measure of reclamation in a chronosequence coal mine overburden spoil. Differentiation between six mine spoil and native forest soil was determined based on microbial enumeration and enzyme activity. The relationship between microbial populations and enzyme activity was analyzed. Kinetic parameters (Vmax and Km) have greater significance as early and sensitive indicators to assess changes in microbial activity representing quantity and affinity of soil enzymes (amylase: 2.013-12.629; invertase: 8.193-411.528; protease: 2.949-75.942; urease: 2.544-29.307; phophatase; 3.106-53.608 and dehydrogenase: 0.225-2.129). The catalytic efficiency (Vmax/Km) was estimated to be higher in NF as compared to mine spoil, which reflects an impression on microbial community with a change in soil enzymes. Principal component analysis was performed to discriminate soil profiles, which holds potential as complementary criteria for evaluating the progress of reclamation.